2018
DOI: 10.1017/s175173111700163x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrient restriction during early or mid-gestation without realimentation on maternal physiology and foetal growth and development in beef cattle

Abstract: The aim of this study is to determine the effects of early and mid-gestation nutrient restriction on maternal metabolites and foetal growth. Primiparous Angus cows were synchronized and inseminated with semen from one sire. Dietary treatments were: control to gain 1 kg/week (CON) or 0.55% maintenance energy and CP requirements (nutrient restricted; NR). A subset of dams was fed NR (n=8) or CON (n=8) from days 30 to 110 of gestation. Another group was fed CON (n=8), days 30 to 190; NR (n=7), days 30 to 110 foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
10
0
3
Order By: Relevance
“…Because males have higher growth and metabolism than females (Clarke and Mittwoch 1995), this may have altered sensitivity to the diet restriction. This finding is consistent with previous reports of sex-specific effects of dietary perturbation in early gestation on bovine fetal development (Micke et al 2015;Taylor et al 2018). In contrast, studies investigating perturbations occurring during the second trimester in the bovine (Miguel-Pacheco et al 2017) and in the second and third trimesters in humans (Clifton 2010) report that the female is more responsive.…”
Section: Placental Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…Because males have higher growth and metabolism than females (Clarke and Mittwoch 1995), this may have altered sensitivity to the diet restriction. This finding is consistent with previous reports of sex-specific effects of dietary perturbation in early gestation on bovine fetal development (Micke et al 2015;Taylor et al 2018). In contrast, studies investigating perturbations occurring during the second trimester in the bovine (Miguel-Pacheco et al 2017) and in the second and third trimesters in humans (Clifton 2010) report that the female is more responsive.…”
Section: Placental Parameterssupporting
confidence: 92%
“…Although the mechanisms behind this effect are not clear, the reported sex-specific differences in uterine artery flow, Doppler fetoplacental perfusion indices and response of these indices following the maternal dietary interventions in these heifers may have contributed to this finding . In addition, the sex-specific maternal endocrine adaptations to the maternal diet treatments (Copping et al 2020) may represent a placental signalling mechanism enabling changes in fetoplacental growth, as noted previously in humans (Hodyl et al 2010) and cattle (Micke et al 2015;Taylor et al 2018).…”
Section: Placental Parametersmentioning
confidence: 79%
See 1 more Smart Citation
“…Krog et al (2018) menyatakan penentuan umur fetus dapat diketahui secara fetometrik dari panjang badan, lebar kepala, panjang kerpala, dapat berbeda hasilnya menurut perbadaan jenis kelamin. Lebih lanjut Taylor et al (2017) mengatakan bahwa banyak faktor yang mempengaruhi berat dan panjang fetus yang dihasilkan seekor ternak induk, diantaranya adalah faktor nutrisi induk, kondisi suhu lingkungan, paritas, dan genotif induk. Misalnya, pembatasan nutrisi yang berlebihan bagi induk selama paruh waktu setengah hingga 2/3 akhir kebuntingan dapat mengurangi pertumbuhan dan perkembangan fetus.…”
Section: Karakteristik Fetus Sapi Yang Dibuangunclassified
“…Long et al [1] described no differences in calf birth weight in underfed dams during early gestation, whereas Micke et al [2] reported reduced calf birth weight in nutrient restricted heifers during the first two thirds of gestation. The peri-implantational period is a vulnerable phase, during which adverse programming mediated through poor maternal nutrition might begin [3,4,5]. Under adverse intrauterine conditions, the fetus could permanently modify some endocrine functions to ensure its survival [6].…”
Section: Introductionmentioning
confidence: 99%